Sale and Purchase Binding Agreement As A Legal Protection On The Sale and Purchase of Mortgaged Land - Hidayat Putri, Zora Febriena Dwithia (Universitas Islam Malang, 2023)
The concept of sale and purchase of land in Indonesian positive law requires it to be made in a Sale and Purchase Deed by a Land Deed Official by first fulfilling the conditions that have been determined. However, in practice, the making of a Sale and Purchase Deed cannot always be done immediately due to requirements that have not been fulfilled by one or even all parties to the agreement. To overcome this condition, the parties can first bind the agreement by making a Sale and Purchase Binding Agreement (PPJB). The objective of the paper is to analyze the position of PPJB as legal protection on the sale and purchase of mortgaged land and to analyze the role of Notary in making PPJB of mortgaged land. In conclusion, as a reciprocal agreement, the PPJB is considered to always have a void condition. If one party does not carry out its obligations, the injured party can demand the implementation of obligations or cancel the agreement, accompanied by compensation for losses, costs and interest. The role of Notary in making PPJB of mortgaged land is to ensure the authenticity of PPJB so that it can be used as perfect evidence and to arrange the clauses in the agreement carefully and accommodate legal protection for the parties in PPJB.